Gamification for Social Innovation: A Behavioral Experiment in Urban Youth Entrepreneurship - Ferdianty Augustinah; Aom Thai; Siri Lek (Journal of Loomingulisus ja Innovatsioon, 2025)
Engaging urban youth in social entrepreneurship presents a significant challenge, often hindered by perceived complexity and a lack of motivational frameworks. This study investigates the potential of gamification to foster social innovation and entrepreneurial behaviors among this demographic. The primary objective was to experimentally measure the impact of a gamified intervention on the pro-social entrepreneurial intentions and idea generation quality of urban youth. This research employed a behavioral experiment with a pre-test/post-test control group design, involving 150 urban youths aged 18-24. The experimental group interacted with a gamified digital platform designed to guide them through social venture creation, incorporating points, badges, and collaborative leaderboards. In contrast, the control group used a non-gamified version of the same platform. The results revealed that participants in the gamified condition demonstrated significantly higher levels of engagement, produced more innovative and viable social solutions, and reported a greater increase in entrepreneurial self-efficacy compared to the control group. In conclusion, gamification serves as a powerful and effective strategy to lower entry barriers and motivate urban youth, channeling their creativity toward developing impactful social innovations and fostering a new generation of community-focused entrepreneurs.